Politics of belonging and the Eritrean diaspora youth: Generational transmission of the decisive past. Issue 92 (June 2018) - Graf, Samuel
Abstract: This article addresses the generational transmission of the decisive Eritrean past and illustrates its influence on the reinforcement and maintenance of Eritrean identity and sense of belonging to Eritrea on young Eritreans grown up in the diaspora. It argues that the transmission and preservation of narratives and knowledge about the decisive Eritrean past makes the Eritrean history a "chosen trauma", which constitutes an important aspect of the formation of a collective identity. Thereby, the article focuses on two particular modes of transmissions: first, within families from parents to children and second, by the international conferences of the YPFDJ, the exile youth branch of the country's ruling People's Front for Democracy and Justice PFDJ. The generational transmission of a decisive past helps to understand the formation of identity and belonging of second-generation Eritreans and further contributes to the broader debate on post-migrant generations constituting belonging in a transnational field.